Local Resources Development: Model Pembangunan Desa Berbasis Sumber Daya Lokal Untuk Menekan Angka Migrasi Internasional - Yuyun Fitriani; Ari Gusnita; Eka Gustinasari; Hasbi Maulana Yusuf; Jordan Aditya Radenda; Sulistiani Sulistiani (Jurnal Administrasi Politik dan Sosial, 2025)
This study is motivated by the high number of productive-age residents in Kota Metro who choose to work abroad, while villages still need productive human resources to develop their local potential. The research aims to analyze a Local Resources Development (LRD) model as an effort to reduce international migration. Using a descriptive qualitative method through document studies and interviews, the findings show that the utilization of local potential such as agriculture, micro, small and medium enterprises (MSMEs), and the creative economy has not been optimal and therefore has not reduced migration pressures. Migration is further driven by the seasonal nature of agriculture, limited MSME capital, and the lack of technological and digital marketing support. The proposed LRD model emphasizes the use of natural resources, strengthening of creative economies based on local wisdom, capacity-building for human resources, and collaboration between government and the private sector. This model is expected to provide sustainable employment alternatives and improve community welfare, thereby reducing international migration.